MEMBACA ULANG PEMAKNAAN KEADILAN SOSIAL DALAM GAGASAN REVOLUSI HUKUM SOEDIMAN KARTOHADIPRODJO - Shidarta, Shidarta (Veritas et Justitia, 2015)
AbstractSoediman Kartohadiprodjo was one of few Indonesian legal scholars taking interest in Pancasila, the state ideology  promulgated by Soekarno. Soediman believe that social justice, the core concept of Pancasila corresponds with the “kekeluargaan” principle as found in the constitution.  However, he used the the term welfare or happines rather than social justice since the latter, according to him, tends to adopt liberalist and individualist principles, which according to him contradicts with Pancasila.  He also endorsed the idea of “legal revolution”as a mean to increase the Indonesian populace’ awareness about recent legal development post independence. This article discusses and critizes Soediman’s idea on social justice and legal revolution. Keywords: Pancasila, social justice, welfare state, law revolution.